Dinamika Pertumbuhan Ekonomi di Indonesia: Peran Sektor Perbankan, Pembentukan Modal Tetap Bruto, Perdagangan Internasional, dan Kualitas Pendidikan - Prasetiyo, Abyan Tsabit Ubaidah; Arief Bachtiar (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Indonesia, with its vast territory and various provinces, has diverse economic growth. GDP is a common indicator for measuring progress, and the banking sector plays an important role in the country's development. International trade, including exports and imports, also influences economic growth. The quality of education is also an important factor, because a high level of education can increase the efficiency of production of goods and services, as well as the quality of workers. The aim of this research is to determine the influence of the banking sector, Gross Fixed Capital Formation (GFCF), international trade and quality of education on economic growth in Indonesia. The data used is secondary data for the period 1973-2022 obtained from the World Bank, Bank Indonesia and Ototritas Jasa Keuangan (OJK). The analysis used is the Vector Error Correction Model (VECM). The results of this research show that there is a positive and significant influence of total national banking assets, GFCF, and exports on economic growth. Meanwhile, the imports and quality of education has a negative and significant effect on economic growth